White blood count in patients on regular haemodialysis. Issue 5675 (11th October 1969) - Papadimitriou, M.; Baker, L. R. I.; Seitanidis, B.; Sevitt, L. H.; Kulatilake, A. E.
Abstract : Total white cell, neutrophil, and lymphocyte counts were compared in patients with chronic renal failure treated successively by conservative means (low-protein diet), regular haemodialysis, and renal allotransplantation. The lowest total white cell and neutrophil counts and the highest lymphocyte counts were found in patients on regular haemodialysis. A rapid fall in neutrophil count during the first half-hour of dialysis and a more gradual fall between the first and sixth hours were observed. Adherence of neutrophils and mononuclear cells to the cuprophane (PT 150) dialysis membrane has been shown.